2023
DOI: 10.3390/antiox12020234
|View full text |Cite
|
Sign up to set email alerts
|

An Interplay between Oxidative Stress (Lactate Dehydrogenase) and Inflammation (Anisocytosis) Mediates COVID-19 Severity Defined by Routine Clinical Markers

Abstract: Viral infections activate the innate immune response and the secretion of inflammatory cytokines. They also alter oxidative stress markers, which potentially can have an involvement in the pathogenesis of the disease. The aim of this research was to study the role of the oxidative stress process assessed through lactate dehydrogenase (LDH) on the severity of COVID-19 measured by oxygen saturation (SaO2) and the putative interaction with inflammation. The investigation enrolled 1808 patients (mean age of 68 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The increase in LDH as a nonspecific enzyme, starting from the eighth day of SARS-CoV-2 infection, has been reported in studies in the literature, and it has been the most important risk factor for mortality in COVID-19 patients [ 24 ]. Furthermore, in COVID-19 infection, LDH levels as a marker of oxidative stress have been shown to correlate with ambient oxygen saturation, anisocytosis, and disease severity [ 25 ]. Another acute-phase protein is fibrinogen, the precursor of fibrin, which consists of two subunits with three polypeptide chains of Aalpha, Bbeta, and γ.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in LDH as a nonspecific enzyme, starting from the eighth day of SARS-CoV-2 infection, has been reported in studies in the literature, and it has been the most important risk factor for mortality in COVID-19 patients [ 24 ]. Furthermore, in COVID-19 infection, LDH levels as a marker of oxidative stress have been shown to correlate with ambient oxygen saturation, anisocytosis, and disease severity [ 25 ]. Another acute-phase protein is fibrinogen, the precursor of fibrin, which consists of two subunits with three polypeptide chains of Aalpha, Bbeta, and γ.…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between inflammatory biomarkers and prognosis in COVID-19 patients undergoing Azvudine treatment remains unclear.Lactate dehydrogenase (LDH), a cytoplasmic glycolytic enzyme found in almost every tissue, is commonly used as an indicator of tissue damage ( Jurisic et al., 2015 ). Numerous studies have shown that elevated LDH levels are positively associated with the severity of COVID-19 ( Bartziokas and Kostikas, 2021 ; Szarpak et al., 2021 ; Alonso-Bernáldez et al., 2023 ; Ergenc et al., 2023 ). However, it is still uncertain whether LDH can predict the prognosis in COVID-19 patients receiving Azvudine treatment.…”
Section: Introductionmentioning
confidence: 99%